2015
DOI: 10.1039/c5ra20976e
|View full text |Cite
|
Sign up to set email alerts
|

A silver-promoted solid-phase guanidylation process enables the first total synthesis of stictamide A

Abstract: First total synthesis of stictamide A, a structurally unique peptide with a statine motif and a N-prenyl modified arginine in the side chain, is disclosed with a novel silver-promoted solid-phase strategy for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…First, fragment 3a was prepared using a standard HESPPS procedure, with Rink amide resin as the solid support, and Fmoc‐Lys(Alloc)OH was installed at the linkage site (Alloc, allyloxycarbonyl). Then, the Alloc group was removed using Pd[P(Ph) 3 ] 4 and phenylsilane to yield fragment 3b on the resin . Next, another equivalent of Ub[Cys 46 Gly 76 ]OH was attached to the proximal Lys ε‐amine of the linkage site.…”
Section: Resultsmentioning
confidence: 99%
“…First, fragment 3a was prepared using a standard HESPPS procedure, with Rink amide resin as the solid support, and Fmoc‐Lys(Alloc)OH was installed at the linkage site (Alloc, allyloxycarbonyl). Then, the Alloc group was removed using Pd[P(Ph) 3 ] 4 and phenylsilane to yield fragment 3b on the resin . Next, another equivalent of Ub[Cys 46 Gly 76 ]OH was attached to the proximal Lys ε‐amine of the linkage site.…”
Section: Resultsmentioning
confidence: 99%
“…Lithium amidinates are normally prepared in a straightforward manner by addition of lithium alkyls to N,N 0 -diorganocarbodiimides in a 1:1 molar ratio, while lithium guanidinates are formed when lithium-N,N-dialkylamides are added to N,N 0 -diorganocarbodiimides (Stalke et al, 1992;Aharonovich et al, 2008;Chlupatý et al, 2011;Nevoralová et al, 2013;Hong et al, 2013). On the other hand, silver(I) amidinates and guanidinates (Archibald et al, 2000;Lim et al, 2003;Whitehorne et al, 2011;Lane et al, 2014) are of significant importance as potential precursors for vapor deposition processes (Lim et al, 2003;Whitehorne et al, 2011), as precursors for silver nanoparticles (Cure et al, 2015), or as intermediates in silver-catalyzed amidination and guanylation reactions (Pereshivko et al, 2011;Okano et al, 2012;Li et al, 2015).…”
Section: Chemical Contextmentioning
confidence: 99%
“…According to retrosynthetic analysis, researchers found that it was not easy to obtain by either the liquid or solid-phase methods because of the N-prenyl-modified arginine. Therefore, inspired by the arginine-N-glycosylated glycopeptide synthesis method, they finally chose to directly synthesize the amino acid side chains on the solid-phase carrier, and the silver-promoted solid-phase synthesis method successfully synthesized stictamide A ( Li et al, 2015 ). However, the application of silver-promoted solid-phase guanidinylation in cyclic peptides has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%